223=6*x+7

Simple and best practice solution for 223=6*x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 223=6*x+7 equation:


Simplifying
223 = 6x + 7

Reorder the terms:
223 = 7 + 6x

Solving
223 = 7 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
223 + -6x = 7 + 6x + -6x

Combine like terms: 6x + -6x = 0
223 + -6x = 7 + 0
223 + -6x = 7

Add '-223' to each side of the equation.
223 + -223 + -6x = 7 + -223

Combine like terms: 223 + -223 = 0
0 + -6x = 7 + -223
-6x = 7 + -223

Combine like terms: 7 + -223 = -216
-6x = -216

Divide each side by '-6'.
x = 36

Simplifying
x = 36

See similar equations:

| 12.6=x*40 | | 9(-10+x)-5(2x+9)=4-x+11 | | 5x-50=15 | | -19y=2x+.05 | | 6x+2+2-3x=-4(6x-3)+3(-x-3) | | 6a+17=-1 | | -2(2x+5)=-2+4x | | .27=x*75 | | x+.07x=15877 | | (4x+8y^2)(x-y^2)=0 | | 5h+21=11 | | W-19=6+9w | | 4(-4x+6)=-6(1+2x)-x | | X+x*4-144=0 | | -p+5=25-6p | | -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 | | 5d-7=23 | | 7=2x^2+6x+7 | | -3(5+3x)=4x-2 | | B+8=1 | | -.7x+26.9=-x+29 | | 10-x+6x=-x-4x | | -22=-6+k | | 24+8x=40 | | X^2+kx-k+8=0 | | -22=-6+6 |

Equations solver categories